Renewable energy project success in malaysia: the influence of stakeholder engagement indicators with the moderating effect of renewable energy policy implementation - Zarith Sufia, Azlan (2022)
Renewable energy (RE) has grown at a rapid pace in delivering sustainable and clean energy. However, the transition to RE and the development of RE projects are not without challenges, including in Malaysia. The current statistics data reports that the status of RE projects in Malaysia remains underperforming. Therefore, researchers and practitioners are focusing on stakeholder engagement as the enabler towards delivering RE project success. Nevertheless, there is inconsistency in stakeholder engagement practices towards the RE project's success. Thus, this study integrates stakeholder engagement and RE policy implementation in order to identify the interrelationship between the variables in delivering RE project success. Specifically this research empirically examines: (1) the current extent of stakeholder engagement practice in RE projects in Malaysia; (2) the relationship between stakeholder engagement indicators and RE projects' success; (3) the mediating role of stakeholder integration between stakeholder communication, stakeholder learning, and stakeholder relations towards RE project success; and (4) the moderating role of RE policy implementation between stakeholder engagement indicators and RE project success. The methodology adopted in this study is the quantitative method. A total of 309 survey questionnaires were sent out to RE firms registered with the Sustainable Energy Development Authority (SEDA), and 122 completed questionnaires were collected and analysed. This study uses IBM SPSS Ver. 28 and SmartPLS Ver. 3.0 to analyse the data. Based on the findings, it shows that stakeholder engagement indicators have a positive effect on RE project success. The mediating effect of stakeholder integration was found to be partially mediated by stakeholder learning and stakeholder relations towards RE project success. It was further found that the moderating effect of RE policy implementation partially moderated the relationship between stakeholder engagement indicators and RE project success. These findings contributed to the project management literature by integrating stakeholder theory and public policy implementation theory to achieve project success. The introduction of stakeholder engagement indicators guides the RE firms in delivering the stakeholder engagement practice. In addition, the mediating effect of stakeholder integration and the moderation effect of RE policy implementation to improve the RE project's success have also been documented in the literature. Overall, the findings revealed that the relationships among stakeholder engagement, RE policy implementation, and RE project success were strongly significant. These relationships provide great insight to the RE firms, especially for the project management professionals, in strategizing the development of RE projects that result in improving the national target of achieving a sustainable and clean energy country.